PEMBERDAAAAN INDUSTRI KECIL KUE MOCHI OLEH DINAS KOPERASI PERINDUSTRIAN DAN PERDAGANGAN KOTA SUKABUMI PROVINSI JAWA BARAT - Mulyana Mulyana; Bima Suci Nugraha (ipdn, 2018)
The society participation in every empowerment process is key to the success of an mpowerment program. The role of society in process of empowerment process will increase people skill as a result of empowerment, therefore, the author takes the title of “the Empowerment of Mochi cake small Industry by cooperation, Industrial and trade Agency of sukabumi Municipal West Java Province”. The purpose of observation is to identify rate of government succesfull in the Empowerment of Mochi Cakes Small Industry, the influence factors on implementation of that program, and the solutions which can do to improve people skill on empowerment process. The observations was conducted by using exploratory method and inductive approach. The technique of data collection use interview, observation and documentation. The result showed that, the empowerment of mochi cake small indutry which have been done by Cooperation, Industrial and Trade Agency of Sukabumi Municipal certainly, but it felt not optimal by the small industrialists of mochi cakes in Sukabumi constantly. This can be seen by all of program and activity which conducted in the process of empowerment, there are on process of planning, implementing, utilizing and program evaluating. The supporter factors of mochi cakes small industry growth in Sukabumi are character, culture, location, transportation and excellent products. The inhibitor factors of mochi cakes small industry growth in Sukabumi are the high level of competition which make reduce the level of marketing, lack of capital, lack of business concept from mochi’s industrialist and lack skill of Mochi’s maker. The solutions which can do by Sukabumi Municipal Government and the suggestions which can be given by the author to solve each inhibitor factors in mochi cakes small industry at Sukabumi, that enhancing market by promotion, increasing capitalization, increasing business knowledge by meeting companionship of entrepreneur, and improve their skills by training. This things will improve the empowerment result of mochi cake small industry at Sukabumi. Keywords: empowerment, small industry, economy, mochi